Rhythms of life the biological clocks that control the daily lives of every living thing - Foster, Russell G.; Kreitzman, Leon (Yale University Press, 2005)
"Why can't teenagers get out of bed in the morning? How do bees tell the time? Why do some plants open and close their flowers at the same time each day? Why do so many people suffer the misery of jet lag? In this fascinating book, Russell Foster and Leon Kreitzman explain the significance of the biological clock, showing how it has played an essential role in evolution and why it continues to play a vitally important role in all living organisms. The authors tell us that biological clocks are embedded in our genes and reset at sunrise and sunset each day to link astronomical time with an organism's internal time. They discuss how scientists are working out the clockwork mechanisms and what governs them, and they describe how organisms measure different intervals of time, how they are adapted to various cycles, and how light coordinates the time within to the external world. They review problems that can be caused by malfunctioning biological clocks - including jet lag, seasonal affective disorder, and depression." -- Publisher's description